Ectopic expression of single transcription factors directs differentiation of a medaka spermatogonial cell line - Thoma, Eva C.; Wagner, Toni U.; Weber, Isabell P.; Herpin, Amaury; Fischer, Andreas; Schartl, Manfred (Stem Cells and Development, 2011)
The capability to form all cell types of the body is a unique feature of stem cells. However, many questions remain concerning the mechanisms regulating differentiation potential. The derivation of spermatogonial cell lines (SGs) from mouse and human, which can differentiate across germ-layer borders, suggested male germ cells as a potential stem cell source in addition to embryonic stem cells. Here, we present a differentiation system using an SG of the vertebrate model organism Oryzias latipes (medaka). We report differentiation of this cell line into 4 different ectodermal and mesodermal somatic cell types. In addition to differentiation into adipocytes by retinoic acid treatment, we demonstrate for the first time that directed differentiation of an SG can be induced by ectopic expression of single transcription factors, completely independent of culture conditions. Transient transfection with mitf-m, a transcription factor that has been shown to induce differentiation into melanocytes in medaka embryonic stem cells, resulted in the formation of the same cell type in spermatogonia. Similarly, the formation of neuron-like cells and matrix-depositing osteoblasts was induced by ectopic expression of mash1 and cbfa1, respectively. Interestingly, we found that the expression of all mentioned fate-inducing transcription factors leads to recapitulation of the temporal pattern of marker gene expression known from in vivo studies.
Gesehen am 02.11.2022
Erstmals am 19 November 2010 online veröffentlicht